Effects of Compound Attractants on Intestinal Transcriptome, and Microbiota of Mandarin Fish (Siniperca chuatsi) - Yefeng Lv; Qiong Zhou; Jiezhou Zhu; Chunqi Wu; Weiguo Xu; Jianhu Jiang; Xiao Liang; Fuyong Huang (Fishes, 2026)
To evaluate the potential of compound attractants in ameliorating diet-induced intestinal dysfunction in Siniperca chuatsi fed commercial compound feed, this study investigated their effects on intestinal metabolism and microbiota composition. In this study, four distinct diets are formulated: a control diet without attractants and three experimental diets supplemented with compound attractants A (nucleotides and L-glutamic acid), B (nucleotides, L-glutamic acid, and allicin), and C (nucleotides, L-glutamic acid, and betaine). Over a period of 8 weeks, groups of S. chuatsi were fed these diets, after which we assessed the intestinal microbiota and transcriptomic responses. KEGG pathway analysis of differentially expressed genes (DEGs) indicated that the A group exhibited significant changes predominantly in intestinal cholesterol homeostasis and inflammatory responses. The B group showed DEGs primarily associated with mucosal immune functions and pro-inflammatory cytokine signaling. Diversely, the C group revealed DEGs chiefly tied to immune and inflammatory response pathways. Furthermore, the intestinal microbiota exhibited beneficial modifications at both the phylum and genus levels in the A and B groups, while such beneficial shifts were not observed in the C group. These findings indicated that dietary supplementation with compound attractants A and B could positively influence both the intestinal transcriptomic landscape and microbiota composition in S. chuatsi, highlighting their potential as effective additives in compound feeds for aquaculture.